2012
DOI: 10.1002/cbf.2907
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antiapoptotic effects of proanthocyanidin and ginkgo biloba extract against doxorubicin‐induced cardiac injury in rats

Abstract: Grape seed proanthocyanidins (GSPE) and ginkgo biloba extract (EGb761) are considered to have protective effects against several diseases. The cardiotoxicity of doxorubicin (DOX) has been reported to be associated with oxidative damage. This study was conducted to evaluate the cardioprotective effects of GSPE and EGb761 against DOX-induced heart injury in rats. DOX was administered as a single i.p. dose (20 mg kg(-1)) to adult male rats. DOX-intoxicated rats were orally administered GSPE (200 mg kg(-1)  day(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 55 publications
6
46
0
Order By: Relevance
“…Further confirmation comes from another study showing that GSE treatment in combination with DOX in mice significantly protected the heart tissue by improving its antioxidant activity; leading to this conclusion that GSE acts as a potent antioxidant to prevent heart damage. 27,39 In the line with this evidence, Karthikeyan et al have confirmed the efficacy of GSPE as a cardioprotective agent in alleviating isoproterenol-induced myocardial injury in rats. 40 They demonstrated that GSPE administration at doses of 100 and 150 mg/kg positively alters the levels of glutathione, ascorbic acid, a-tocopherol, ceruloplasmin, mitochondrial cytochrome, phospholipids and adenosine triphosphate and also restores normal mitochondrial function.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Further confirmation comes from another study showing that GSE treatment in combination with DOX in mice significantly protected the heart tissue by improving its antioxidant activity; leading to this conclusion that GSE acts as a potent antioxidant to prevent heart damage. 27,39 In the line with this evidence, Karthikeyan et al have confirmed the efficacy of GSPE as a cardioprotective agent in alleviating isoproterenol-induced myocardial injury in rats. 40 They demonstrated that GSPE administration at doses of 100 and 150 mg/kg positively alters the levels of glutathione, ascorbic acid, a-tocopherol, ceruloplasmin, mitochondrial cytochrome, phospholipids and adenosine triphosphate and also restores normal mitochondrial function.…”
Section: Discussionmentioning
confidence: 88%
“…The animal model used in this study was described previously 21 and characterized by injuries similar to what reported by others. 17,18,[25][26][27] Alterations in physiological parameters are well known as one of the toxic effects of DOX, which is characterized by reduced body and heart weights. [28][29][30] Our findings here confirmed the literature reports that DOX treatment leads to decreased both body and heart weights in animals 31 and that GSE treatment increased body and heart weights, as compared to DOX group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doxorubicin increases myocardial lipid peroxidation and decreases glutathione peroxidase levels early in doxorubicin cardiotoxicity [12,13]. Myocardium is more susceptible to oxidative damage than other tissues as it contains low levels of catalase and glutathione peroxidase.…”
Section: Introductionmentioning
confidence: 99%
“…G. biloba extract (GbE), isolated from the dried leaves of G. biloba, has been reported to have many beneficial activities, including free radical scavenging (Wang et al, 2010), antioxidative (Boghdady, 2013), anti-inflammatory (Chen et al, 2013b), anti-tumor activities (Tsai et al, 2014), and neuroprotective effects (Abd-Elhady et al, 2013). GbE has become one of the best-selling botanical supplements in many European countries and in the USA for the prevention and adjunctive treatment of vascular and cognitive diseases, such as Alzheimer's disease (Oken et al, 1998;Tchantchou et al, 2007), vertigo (Hamann, 2007;Sokolova et al, 2014), tinnitus (Hilton et al, 2013;Tziridis et al, 2014), and peripheral arterial occlusive diseases (Unger, 2013;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%